(untitled) (E Global Congress, 2025)
This study presents the development and evaluation of an additional mechanism aimed at improving fabric quality by stabilizing warp yarn tension in weaving machines. Uneven and unstable warp tension is one of the major factors negatively affecting fabric strength and increasing yarn breakages during weaving. To address this issue, a flexible-cylinder-based device was designed, in which the wrapping arc length of the warp yarn wound along the cylinder’s perimeter can be adjusted depending on shed volume, weave type, and the process of beating the weft yarns to the fabric edge. This adjustment allows the creation of uniform warp yarn tension throughout the shed formation process.